(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2014)
Urbanization rates across the world economy are now higher and more rapid than ever before in human history. What categories and models of urbanization are most appropriate for understanding these transformations, their origins, and their consequences, and for coming to terms with their wide-ranging implications? In this brief essay, we cannot attempt to survey the intricacies of diverse research traditions. Instead, we outline some of the methodological foundations and major lines of investigation within research on globalizing cities, while also alluding to several emergent debates and agendas that are currently animating this field, with specific reference to the conceptualization and investigation of global interurban networks.